The Influence of TikTok Video Content and Live Streaming on Patient Consultation Decisions at Indonesian Men's Clinics - Putra, Alamsyah; Zaharuddin, Zaharuddin; Kusuma, Sitta (IJBLE Scientific Publications Community Inc., 2026)
This study aims to examine the influence of TikTok video content (X1) and live streaming (X2) on patients’ consultation decisions (Y) at Klinik Lelaki Indonesia. The research employed a quantitative approach using purposive sampling, involving 154 respondents. Data were analyzed using SPSS version 25, including validity testing, reliability testing, classical assumption testing, and multiple regression analysis. The results indicate that all research instruments were valid (r > 0.159; p < 0.05) and reliable (Cronbach’s Alpha values: X1 = 0.745; X2 = 0.821; Y = 0.682). Furthermore, the regression model satisfied classical assumption tests, including normality (p = 0.156), multicollinearity (VIF = 1.885), and autocorrelation (Durbin–Watson = 1.619). The partial regression analysis shows that video content (B = 0.273; p < 0.001) and live streaming (B = 0.267; p < 0.001) have positive and significant effects on consultation decisions. Simultaneously, both variables significantly influence consultation decisions (F = 55.633; p < 0.001). The coefficient of determination (R² = 0.424) indicates that 42.4% of the variance in patient consultation decisions is explained by the two independent variables, while the remaining 57.6% is accounted for by factors outside the model. These findings suggest that improving the quality and effectiveness of digital health content on social media platforms increases patients’ likelihood of seeking medical consultation.